2000
DOI: 10.1126/science.289.5483.1340
|View full text |Cite
|
Sign up to set email alerts
|

Galileo Magnetometer Measurements: A Stronger Case for a Subsurface Ocean at Europa

Abstract: On 3 January 2000, the Galileo spacecraft passed close to Europa when it was located far south of Jupiter's magnetic equator in a region where the radial component of the magnetospheric magnetic field points inward toward Jupiter. This pass with a previously unexamined orientation of the external forcing field distinguished between an induced and a permanent magnetic dipole moment model of Europa's internal field. The Galileo magnetometer measured changes in the magnetic field predicted if a current-carrying o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
346
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(380 citation statements)
references
References 16 publications
7
346
0
3
Order By: Relevance
“…For Callisto, the perturbation cannot be explained by a permanent dipole field. For Europa, measurements from pass E26, while the moon was in the opposite magnetic hemisphere, have also definitely excluded a permanent dipole moment (Kivelson et al 2000). The magnetic signatures at both moons are consistent with more than 70% of the induced dipole moment expected for perfectly conducting spheres the size of the moons.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…For Callisto, the perturbation cannot be explained by a permanent dipole field. For Europa, measurements from pass E26, while the moon was in the opposite magnetic hemisphere, have also definitely excluded a permanent dipole moment (Kivelson et al 2000). The magnetic signatures at both moons are consistent with more than 70% of the induced dipole moment expected for perfectly conducting spheres the size of the moons.…”
Section: Resultssupporting
confidence: 62%
“…However, a strong test of the induction model was provided by the recent flyby E26 on January 3, 2000, during which the jovian field had an orientation roughly opposite to that during encounters E4 and E14. Kivelson et al (2000) showed that the observed field perturbations are indeed in much better agreement with the induced dipole model than with a permanent dipole moment capable of accounting for the E4 and E14 data.…”
Section: Phase Lagmentioning
confidence: 73%
“…[2] The presence of a subsurface ocean on Europa is strongly implied by Galileo spacecraft magnetometer data indicative of a magnetic field due to currents induced in a near-surface saline liquid water layer [Kivelson et al, 2000]. A wide range of imaging data also suggests the presence of an ocean, including the sparsity of impact craters; lowsurface relief with lateral separation of crustal plates [Lucchita and Soderblom, 1982;Greeley et al, 1998]; models for the formation of flexi by periodic tidal stresses [Hoppa et al, 1999]; and crater morphologies [Moore et al, 1998;Turtle et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…However, the method here described can be used as an approximation, since the surface heat fl ow of Europa must be mostly generated in the warm ice of the convective sublayer (Ruiz 2005). So, here I take Ti = Tb, where Tb is the temperature at the shell base, which in turn is given by the water ice melting point, as there are solid evidences for an internal ocean on Europa (e.g., Kivelson et al 2000), which depends on pressnre P as (Chizhov 1993)…”
Section: Convective Modelmentioning
confidence: 99%